Acoustic analysis of voice in post-tonsillectomy patients (Bangladesh Journal of Medical Science, 2018)
Introduction: Tonsillectomy is a common surgical procedure performed in otolaryngology setting worldwide. It is a procedure to remove the palatine tonsils, which are one of the major structures in the oropharynx which constitute part of the vocal tract. The study aimed to determine acoustic changes in post-tonsillectomy patients.Methodology: Voice sampling was collected using Praat software before and after operation, which was one day before operation and within 2-3 weeks after the operation respectively. Acoustic parameters including fundamental frequency, jitter, shimmer, harmonic to noise ratio and first formant frequency were analyzed by using paired t-test.Results: A total of 27 participants that underwent tonsillectomy or adenotonsillectomy were involved in this study. The age range of participants was 3-56 years old. The mean age of study was 18.57. There was no significant difference for all the acoustic parameters between pretonsillectomy and post tonsillectomy. However, there were noticeable voice changes through auditory as perceived by participants or caregiver.Conclusion: Although patient and care givers do notice a significant voice changes, but objectively this finding is not reveals during objective voice assessment.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.382-387